PRIVATE FOREST DEVELOPMENT PROSPECT IN JAYAPURA REGENCY, PAPUA - Irma Yeny; Sandhi Imam Maulana (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2010)
Land availability in Jayawijaya District is not directly opening the opportunity for developing community forest in this region. The main factors that influencing the success of community forest development are the selection of appropriate species, the silviculture technique that implemented and the financial feasibility of it. This research conducted in Jayawijaya District and itaim to investigating technical, socio-culture, and financial feasibility in developing community forest in this region. Collected data are tabulated and calculated by using Microsoft Excel Program. The calculations of Net Present Value (NPV), Benefit Cost Ratio (BCR), Internal Rate of Return (IRR) are worked for private forest with pure exertion system in Ibele's forest region. Besides that, Land Expectation Value (LEV) is also calculated by using Faustmann formula. Processed data are analyzed descriptively.The result of this research reveals that (a.) based on forest area allocation there are 198.515 ha available for developing private forest, (b.) there is planting culture as the part of cultivation technique exertion of Dani tribe in Jayawijaya District, (c.) based on financial feasibility study, the exertion of private forest are feasible for 15 years and 25 years cycle scenarios with 5% and 10% discount rates. The 25 years cycle scenario with 5% discount rate has the largest value of LEV, which is Rp. 61.371.850,19/ha